Research progress of exosomes in orthopedics - Zhang, Liang; Lin, Yi; Zhang, Xiannan; Shan, Chen (Frontiers in Genetics, 2022)
Exosomes are nano-extracellular vesicles secreted by a variety of cells. They are composed of a double-layer membrane that can transport a variety of proteins, coding and non-coding genes, and bioactive substances. Exosomes participate in information transmission between cells and regulate processes such as cell proliferation, migration, angiogenesis, and phenotypic transformation. They have broad prospects in the occurrence, development, and treatment of many diseases including orthopedics. Exosomes derived from different types of bone cells such as mesenchymal stem cells, osteoblasts, osteoclasts, and their precursors are recognized to play pivotal roles in bone remodeling processes including osteogenesis, osteoclastogenesis, and angiogenesis. This articlesummarizes the characteristics of exosomes and their research progress in bone remodeling, bone tumors, vascular skeletal muscle injury, spinal cord injury, degenerative disc diseases, cartilage degeneration, osteoarthritis, necrosis of the femoral head, and osteoporosis.